DEVELOPMENT OF HIGHER ORDER THINKING SKILL TEST INSTRUMENTS ON OPTICAL MATERIALS - Mira Surya Ningsih; Wawan Bunawan; Irham Ramadhani (IPER (Indonesian Physics Education Research), 2020)
This study aims to develop HOTS (Higher Order Thinking Skill) test instruments that are able to measure the level of students' critical and creative thinking skills in optical material. The research method used is the ADDIE Research and Development method (Analysis, Design, Development, Implementation, & Evaluate). The research subjects used students from Medan An-Nizam Private High School T.P 2018/2019. The study produced 20 items of test instruments consisting of multiple choices and essays showing that HOTS thinking skills (Higher Order Thinking Skill) from the study sample amounted to 39 people were 18% of students had creative thinking skills, 23% of students had Creative-Critical thinking skills, 54% of students had skills critical thinking, and 5% of students with superior skills are critical.Keywords: Development of HOTS Test Instrument, Optical Material, ADDIE Method.